A Photoelectrochemical Solar Cell Consisting of a Cadmium Sulfide Photoanode and a Ruthenium–2, 2′‐Bipyridine Redox Shuttle in a Non‐aqueous Electrolyte1. (26th May 2015) - Kageshima, Yosuke; Kumagai, Hiromu; Minegishi, Tsutomu; Kubota, Jun; Domen, Kazunari
Abstract A photoelectrochemical (PEC) cell consisting of an n‐type CdS single‐crystal electrode and a Pt counter electrode with the ruthenium–2, 2′‐bipyridine complex [Ru(bpy)3]2+/3+ as the redox shuttle in a non‐aqueous electrolyte was studied to obtain a higher open‐circuit voltage (VOC) than the onset voltage for water splitting. A VOC of 1.48 V and a short‐circuit current (ISC) of 3.88 mA cm−2 were obtained under irradiation by a 300 W Xe lamp with 420–800 nm visible light. This relatively high voltage was presumably due to the difference between the Fermi level of photo‐irradiated n‐type CdS and the redox potential of the Ru complex at the Pt electrode. The smooth redox reaction of the Ru complex with one‐electron transfer was thought to have contributed to the high VOC and ISC. The obtained VOC was more than the onset voltage of water electrolysis for hydrogen and oxygen generation, suggesting prospects for application in water electrolysis.